Utilization of macrocyclic peptides to target protein-protein interactions in cancer - Yang, Jiawen; Zhu, Qiaoliang; Wu, Yifan; Qu, Xiaojuan; Liu, Haixia; Jiang, Biao; Ge, Di; Song, Xiaoling (Frontiers in Oncology, 2022)
Protein-protein interactions (PPIs) play vital roles in normal cellular processes. Dysregulated PPIs are involved in the process of various diseases, including cancer. Thus, these PPIs may serve as potential therapeutic targets in cancer treatment. However, despite rapid advances in small-molecule drugs and biologics, it is still hard to target PPIs, especially for those intracellular PPIs. Macrocyclic peptides have gained growing attention for their therapeutic properties in targeting dysregulated PPIs. Macrocyclic peptides have some unique features, such as moderate sizes, high selectivity, and high binding affinities, which make them good drug candidates. In addition, some oncology macrocyclic peptide drugs have been approved by the US Food and Drug Administration (FDA) for clinical use. Here, we reviewed the recent development of macrocyclic peptides in cancer treatment. The opportunities and challenges were also discussed to inspire new perspectives.